DesignDesign : furniture & lights - Asensio, Oscar (DesignDesign, 2007)
What constitutes good design? Is it form? Is it function? Is it tradition? This title leads the reader on a tour of the furniture designs of the 20th century, from chairs and sofas to end tables and coffee tables to beds to lamps. It provides a survey of contemporary designs for the home and office